The effects of ionic liquids on the properties of epoxidized natural rubber based polymer electrolyte systems / Norazlin Zainal - Norazlin , Zainal (2018)
The objective of this research work is to investigate the effect of ionic liquid on epoxidized natural rubber 50 added with lithium imide salt system. Electrolyte films were prepared using two different methods, namely, the wet method and dry method. Attenuated total reflectance-Fourier transform infrared spectroscopic analyses showed evidence of interaction between epoxidized natural rubber 50, ionic liquid and lithium salt. X-ray photoelectron spectroscopy study was done to strengthen those results. The thermogravimetric analyses of the films containing ionic liquid showed good thermal stability up to 350 C. Glass transition temperatures for the electrolyte films containing ionic liquid were lower than that of ionic liquid free electrolyte films. Addition of lithium salt to the epoxidized natural rubber-ionic liquid systems, with increasing of salt content, increased the glass transition temperature values. The increasing trend of glass transition temperature with increase in salt concentration indicated reduction in flexibility of the polymer chains due to the formation of transient cross-linking between the polymer chains and lithium cation. However, the trend of variation of ionic conductivity showed that the increase in glass transition temperature did not give adverse effect on ionic conductivity. Ionic conductivity of the films increased with salt content. Electrolyte film containing ionic liquid, prepared by wet method showed the highest value in the order 10-4 S cm-1 at ambient temperature. Electrolyte film prepared by dry method could withstand high temperature (for elevated temperature measurement) compared with the electrolyte film prepared by wet method. It was observed from this study that the addition of ionic liquid to polymer-salt system could reduce glass transition temperature and improve ionic conductivity of the